"Der Mensch hat das Wort" : der Sprachdiskurs in der Frankfurter Zeitung 1933-1943 - Dodd, John William (De Gruyter, 2013)
This book contains a selection of annotated glosses and texts on the subject of language that were published in the Frankfurter Zeitung during the Nazi period in an attempt to bypass official censorship. An extensive introduction elucidatesthe position of the paper in the media landscape of the Third Reich, contemporary controversies concerning "internal emigration," and the problematics of writing and reading "between the lines."